2017
DOI: 10.1111/oik.04233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role and measures of juvenile growth rate: latitudinal variation in insect life histories

Abstract: Latitudinal and elevational trends in body size are found in numerous animal taxa, with various adaptive explanations proposed. It is however debatable whether geographic trends in adult body size are accompanied by corresponding differences in juvenile growth rate (= mass gain per unit time). Respective studies have been complicated by conceptual and methodological problems related to defining and measuring this variable, particularly in organisms with discontinuous growth like arthropods. Using an original m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 106 publications
(184 reference statements)
3
21
0
Order By: Relevance
“…For Lepidoptera in particular, several studies report genetically based geographical differences in body size. Larger sizes at lower latitudes – the pattern characteristic of E. atomaria – has been found frequently (Blanckenhorn & Demont, ; Nygren et al., ; Meister et al., ) but not universally (Chown & Gaston, ; Kivelä et al., ; Barton et al., ; Horne et al., ). With one notable exception (Arnett & Gotelli, ), the among‐population difference documented in most previous studies were substantially smaller than the almost two‐fold mass difference detected for E. atomaria in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Lepidoptera in particular, several studies report genetically based geographical differences in body size. Larger sizes at lower latitudes – the pattern characteristic of E. atomaria – has been found frequently (Blanckenhorn & Demont, ; Nygren et al., ; Meister et al., ) but not universally (Chown & Gaston, ; Kivelä et al., ; Barton et al., ; Horne et al., ). With one notable exception (Arnett & Gotelli, ), the among‐population difference documented in most previous studies were substantially smaller than the almost two‐fold mass difference detected for E. atomaria in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Rearing E. atomaria under common garden conditions was part of a more comprehensive study on latitudinal gradients in multiple lepidopteran species. Accordingly, some of the data on E. atomaria have previously been used in another context (Meister et al, 2017).…”
Section: Common Garden Rearingmentioning
confidence: 99%
“…In the study area, the species is most abundant in coniferous forests and on peat bogs where, due to their abundance, dwarf shrubs from the family Ericaceae must serve as primary host plants. There is no evidence of geographical differences in host preference (Meister et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…The criteria for inclusion of a particular species was a broad distribution covering both northern and southern Europe (Meister et al, 2017), sufficient abundance to allow us to obtain rearing material with reasonable effort, and the absence of known ecological differences across the European range. For the present immunological study, we had to limit ourselves to the subset of larger-bodied species which facilitated obtaining sufficient haemolymph.…”
Section: Materials and Methods Study Insectsmentioning
confidence: 99%
“…This is considered the most adequate characteristic of the 'free' growth period in the beginning of an instar; that is, the growth that is not yet affected by physiological preparations for pupation (Ayres and MacLean, 1987;Esperk and Tammaru, 2004;Tammaru et al, 2010). From the mass data, DGR was calculated as (final mass 1/3 -initial mass 1/3 )/time, where time was in days (Meister et al, 2017), with the cube root transformation having been suggested to linearise larval growth curves of lepidopteran larvae (Tammaru and Esperk, 2007). Development time within the last instar was measured by counting the number of days from the beginning of the final instar to the formation of prepupae.…”
Section: Variables Recorded and Statistical Analysesmentioning
confidence: 99%